To Steal or Not to Steal: Self-Discrepancies as a Way to Promote Pro-social Behavior: The Moderating Role of Self-Interest - Gavreliuc, Alin; Gavreliuc, Dana; Semenescu, Alin (Frontiers in Psychology, 2022)
Previous research showed that acting immorally on one occasion can determine a greater availability for pro-social behavior on a subsequent occasion. Nevertheless, moderating factors for this effect such as financial interest remained largely unexplored. The present field experiment (N = 587) was organized in an urban setting, in a post-communist society (Romania), in a context of public anonymity and examined passersby’s pro-social behavior on two consecutive occasions. The procedure involved a confederate “losing” a banknote of different values (1, 10, 50, 100 or 500 RON), which invited passersby’s pro-social behavior to return it (or not). Participants who decided to steal the banknote were approached by a second confederate and asked politely to return the banknote. Our research was articulated mainly as a quantitative approach by measuring participants’ pro-social behavior towards the person who lost the banknote, their subsequent pro-social behavior towards the confederate who exposed their behavior and the number of words they produced during a post-experimental interview in which they could justify their behavior. At the same time we also performed a qualitative approach, through which we explored the themes evoked in their justifications and their relation with their previous behavior. Results indicate a moderating effect of economic interest on pro-social behavior towards the confederate who lost the banknote, as well as on their subsequent pro-social behavior towards the second confederate. Participants who stole the banknote also used significantly more words to justify their behavior, and this tendency could be observed especially in the case for higher values of the banknote. Results are critically discussed in a context dominated by an inherited pattern of distrust and social cynicism.